O maior festival folclórico de todos os tempos: a retomada da economia em Parintins na primeira festa de Boi pós covid-19 - Júnior, Francinaldo (ICSEZ - Instituto de Ciências Sociais, Educação e Zootecnia (Parintins), 2022)
The Parintins Folkloric Festival is one of the most important festivities in the municipality, as it generates employment and income for local citizens and for those who come from other locations. However, in the years 2020 and 2021, the Government of the State of Amazonas and the Prefecture of Parintins decided to suspend the event due to the Covid-19 pandemic. So, the city stopped. Many entrepreneurs and enterprises had to adapt to this situation, trying to circumvent the moment, however, with difficulty, as a large portion of these workers felt the negative impact of this stoppage. In 2022, with the drop in transmission of the Covid-19 virus due to vaccinations in several stages, the competent bodies decided to hold the Festival, news received with relief and expectation for this return. For this, many of these entrepreneurs, whether in formal or informal services, had to reinvent themselves. For everyone, the return of the Folkloric Festival of Parintins rekindled the flame of hope for better days for the citizens who survive financially from this very important festival in the State of Amazonas. To tell these stories, we produced this audiojournalistic product in radio documentary format, in which we interviewed workers, entrepreneurs and self-employed people from various sectors of the municipality's economy. From the production, we can conclude that the economy of Parintins is based on the realization of the Folkloric Festival of Parintins, after all, in the event season, there is generation of work and income.